2002
DOI: 10.1023/a:1017991313789
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The aim of this study was to determine whether an indirect noninvasive indicator of proximal bacterial overgrowth, the glucose breath test, was of diagnostic value in inflammatory bowel disease. Twenty four of 71 Crohn's disease patients tested had a positive glucose breath test. No statistical conclusions could be drawn between the Crohn's disease activity index and glucose breath test status. Of patients with radiologic evidence of small bowel stricture(s), 96.0% had a positive glucose breath test, while onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…A comparison of the prevalence of bacterial overgrowth in subgroups of patients with low (CDAI <150), moderate (CDAI = 150–300) and high (CDAI >300) disease activity showed no significant differences. This confirms data reported by Mishkin et al, who found no statistically significant correlation between CDAI and HGBT results in patients with CD [10]. …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…A comparison of the prevalence of bacterial overgrowth in subgroups of patients with low (CDAI <150), moderate (CDAI = 150–300) and high (CDAI >300) disease activity showed no significant differences. This confirms data reported by Mishkin et al, who found no statistically significant correlation between CDAI and HGBT results in patients with CD [10]. …”
Section: Discussionsupporting
confidence: 92%
“…False positive findings may also be returned in patients with prior extensive resection of the small bowel which leads to accelerated intestinal transit as part of a short-bowel syndrome [10]. A false negative HGBT may occur in patients receiving antibiotics or with induced reduction in intestinal bacterial load secondary to bowel preparation, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations